Full-Wave Analysis of Periodic Baffle System in Beamforming Applications - TASINKEVYCH, Yuriy; DANICKI, Eugeniusz (Archives of Acoustics, 2010)
Mixed boundary-value problem for periodic baffles in acoustic medium is solved with help of the method developed earlier in electrostatics. The nice feature of the method is that the resulting matrices are relatively easy for computations and that the results satisfy exactly the energy conservation law. Illustrative numerical examples present the wave-beam steering (in the far-field) in a baffle system that may be considered as a model of one-dimensional ultrasonic transducer array.